Gender in the Afterlife: An Exploration of Dynamic Gender Stereotypes in the Epitaphs of the Merry Cemetery of Săpânţa - Curşeu, Petru L.; Pop-Curşeu, Ioan (Frontiers in Psychology, 2018)
Gender stereotypes are shaped by the roles men and women fulfil in society. Our study uses a cultural artifact analysis and explores the way in which remunerated jobs, development across lifespan and historical time frames influence the content of gender stereotypes. We coded the feminine and masculine attributes in a selection of epitaphs written on the painted crosses of the Merry Cemetery of Săpânţa (Romania) between 1935 and 2010. This novel historical approach allowed us to explore the dynamic nature of gender stereotypes and the extent to which changes in the social context or the social roles have transformed the content of gender stereotypes. We show that during years of social unrest associated with the World War II and the early communist years the masculine attributes are dominant while during the last decades of the communist regime and the post-communist period the feminine attributes become more prevalent. Moreover, people having paid jobs are described as being more masculine than the homemakers. Finally, our results show an increase of masculinity during the lifespan for both male and female as well as an increase of androgyny with age for women and a slight decrease with age for men.